Maeckes logo

<    1      2      3      4      5      6      7      8      9     10    >


Exponential function

You can change an exponential function in a natural exponential function

f (x) = ax = ex ln a = exp (x ln a)

 


Explanation

The logarithm is the inverse of the exponential function and is defined for a > 0, as

a = eln a

Because ax works according to the rules for logarithms and exponents, it applies

ax = (eln a )x = ex ln a

for every real number x. This definition, which contains powers with logarithms, is common for complex numbers.

 


Deutsch   Español   Français   Nederlands   中文